(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This article aims at analyzing the importance of using Mass Media in the classroom and finding the ways how to use Printed and Audio-visual Media. It is the result of an in-depth study, surveys and questionnaires thus trying to make the ideas in this article more trustworthy. It is based not only on the literature review but also on long personal experience. It is a brief description of some practical examples and some tips for novice teachers. Further more, this article tends to deal with some of the key issues of using media in the classroom. Here are included some of the findings of my research work on a post-doctorate Fulbright Program in 2001. The following issues are open for discussion: the importance of Media in general and in education in particular; Media are persuasive and pervasive, newspapers, magazines, radio, television and internet in the classroom, etc.